2007
DOI: 10.5713/ajas.2007.1444
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Microbial Activities of Faeces from Weaned and Unweaned Pigs in Relation to In vitro Fermentation of Different Sources of Inulin-type Oligofructose and Pig Feed Ingredients

Abstract: An in vitro experiment was conducted to evaluate the differences in microbial activity of five faecal inocula from weaned pigs and one faecal inoculum from unweaned pigs in combination with 6 substrates. The substrates tested were negative control diet, corn, soybean meal, oligofructose (OF), ground chicory roots and a mixture (60% chicory pulp and 40% OF). The inocula used were derived from pigs fed either a corn-soy based diet without antibiotics (NCON), the NCON diet supplemented with oligofructose (OF), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
6
8
0
Order By: Relevance
“…Chicory root and pulp produced lower amounts of total SCFA and butyrate compared to oligofructose and inulin type ingredients due to their amount in fructo‐oligosaccharides, in line with Shim et al . in in vitro studies and Houdijk in in vivo studies.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Chicory root and pulp produced lower amounts of total SCFA and butyrate compared to oligofructose and inulin type ingredients due to their amount in fructo‐oligosaccharides, in line with Shim et al . in in vitro studies and Houdijk in in vivo studies.…”
Section: Discussionsupporting
confidence: 83%
“…Chicory pulp was slowly fermented in comparison to purified fractions (i.e. oligofructose and inulin) while chicory root displayed faster and more extensive fermentation kinetics, as already demonstrated in in vitro batch fermentation studies by Shim et al . and Pellikaan et al .…”
Section: Discussionsupporting
confidence: 60%
“…populations in the distal colon of pigs. Insoluble fibre, which is present in legumes, is slowly fermented in the large intestine and may reduce proteolytic fermentation [71] and promote beneficial alteration in the microbial colonization with a higher butyric acid production in the large intestine and lower enterobacteria count in the digesta [72]. The results of our study also indicated a tendency towards greater isobutyric acid concentration in the colon of animals fed the PE diet.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, it was found that synbiotic preparations increase SCFA production (Shim et al, 2007;Bird et al, 2009) and reduce faecal noxious gas emission (Lee et al, 2009).…”
Section: Synbioticsmentioning
confidence: 99%